2018
DOI: 10.3390/nu10010070
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Carotenoid Intakes and Prostate Cancer Risk: A Case-Control Study from Vietnam

Abstract: The incidence of prostate cancer has increased in Vietnam, but there have been few studies of the risk factors associated with this change. This retrospective case-control study investigated the relation of the intake of carotenoids and their food sources to prostate cancer risk. A sample of 652 participants (244 incident prostate cancer patients, aged 64–75 years, and 408 age frequency-matched controls) were recruited in Ho Chi Minh City during 2013–2015. The habitual diet was ascertained with a validated foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…Lycopene is extremely effective in the fight against the radical of nitric oxide, responsible for damaging lymphocytes . Many studies have indicated that lycopene activity decreases the risk and occurrence of certain diseases for example cardiovascular (by the reduction of lipid peroxidation and the oxidation of low‐density lipoproteins) or epithelial cancers including prostate cancer . Although the relationship between lycopene intake and risk of prostate cancer is controversial …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lycopene is extremely effective in the fight against the radical of nitric oxide, responsible for damaging lymphocytes . Many studies have indicated that lycopene activity decreases the risk and occurrence of certain diseases for example cardiovascular (by the reduction of lipid peroxidation and the oxidation of low‐density lipoproteins) or epithelial cancers including prostate cancer . Although the relationship between lycopene intake and risk of prostate cancer is controversial …”
Section: Introductionmentioning
confidence: 99%
“…4 Many studies have indicated that lycopene activity decreases the risk and occurrence of certain diseases for example cardiovascular (by the reduction of lipid peroxidation and the oxidation of low-density lipoproteins) or epithelial cancers including prostate cancer. 5 Although the relationship between lycopene intake and risk of prostate cancer is controversial. 6 Lycopene synthesis begins by the means of the condensation of two digeranyl diphosphate molecules in the presence of phytoene synthase that results in phytoene forming.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 40 years, there have been numerous and varied studies showing that carotenoids and their derivatives may contribute beneficially to health and reduced the risk for a number of diseases. In the classic carotenoid literature as well as more recent revisions of the original works, carotenoids have been associated with possible benefits to immunity and diseases, including several types of cancers (prostate, breast, cervical, ovarian, colorectal), cardiovascular disease, bone, skin, or eye disorders …”
Section: Importance Of Carotenoids In Agro‐food Health and Diseasementioning
confidence: 99%
“…In the classic carotenoid literature as well as more recent revisions of the original works, carotenoids have been associated with possible benefits to immunity and diseases, including several types of cancers (prostate, breast, cervical, ovarian, colorectal), cardiovascular disease, bone, skin, or eye disorders. [60][61][62][63][64] Long-term supplementation (18 years on average) with 50 mg of β-carotene every other day has also been shown to provide cognitive benefits to an overall apparently healthy population (n = 4052 men, Physicians' Health Study II). [65] The role of lutein and other carotenoids in mental health and cognitive performance is also attracting much attention, [66][67][68][69] as is the role of carotenoids and their derivatives in diabetes mellitus, obesity, and other related metabolic disorders.…”
Section: Carotenoids In Healthmentioning
confidence: 99%
“…Several studies have reported a negative association between intake of carotenoids and risk of PC (Antwi et al, 2016;Van Hoang et al, 2018). Epidemiological studies demonstrated that consumption of fruits and vegetables rich in lutein are inversely related to incidence of prostate cancer ( anticancer effects of lutein could be due to the function of lutein as an antioxidant, a chemo preventative agent or a regulator of apoptosis, angiogenesis and gap junctional intercellular communication (Ribaya-Mercado and Blumberg, 2004).…”
Section: Discussionmentioning
confidence: 99%